High-strength nylon 56 composite fiber and preparation method thereof
By using a catalyst, antioxidant and molecular weight regulator to perform prepolymerization and final polymerization reaction during the spinning process, and mixing it with a binder for melt spinning, high-strength nylon 56 composite fibers are prepared, which solves the problems of spinability and mechanical properties of nylon 56 during the spinning process.
Patent Information
- Application Number
- CN202411866833.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-18
AI Technical Summary
During the spinning process, nylon 56 has problems such as poor spinning ability, high fiber wire breakage rate and poor mechanical properties.
By mixing nylon 56 salt, catalyst, antioxidant, molecular weight regulator with solvent, prepolymerization and final polymerization reaction are performed to obtain nylon 56 polymer, and mixed with binder for melt spinning to prepare high-strength nylon 56 composite fibers.
The strength and mechanical properties of nylon 56 composite fibers are improved, the wire breaking rate is reduced, and the spinability and mechanical properties problems of nylon 56 in the spinning process are solved.
Smart Images

Figure BDA0005194607660000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a high-strength nylon 56 composite fiber and a preparation method thereof. Background Art
[0002] At present, the commonly used spinning method is direct melt spinning, but direct melt spinning generally has problems such as poor spinnability, high fiber breakage rate and poor mechanical properties. For nylon 66 (PA66), due to the excessively fast crystallization rate, its dyeing uniformity is more difficult to control during melt spinning, especially when spinning fine denier yarns; at the same time, due to the high melting point and structural reasons of PA66, its thermal stability is poor, and it is easy to undergo thermal degradation reactions at temperatures above the melting point under anaerobic conditions, accompanied by cross-linking reactions. The cross-linking reaction will further generate gel, which will affect the pipeline transportation of PA66 in industrial production and subsequent spinning work, causing economic losses to the company. The above problems make the spinning cost of PA66 relatively high.
[0003] Nylon 56 (PA56) is a good substitute for PA66 and can reduce processing costs. Currently, it is used by a large number of companies. However, due to the short molecular chain of PA56, it is prone to broken yarns and unevenness during the spinning process. Its breaking strength is not as good as that of long-chain nylon, and its mechanical properties are poor. It generally has problems of poor strength and toughness. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength nylon 56 composite fiber and a preparation method thereof, so as to solve the problems of poor spinnability, high fiber breakage rate and poor mechanical properties of nylon 56 in the conventional spinning process.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing high-strength nylon 56 composite fiber, comprising the following steps:
[0007] (1) mixing nylon 56 salt, a catalyst, an antioxidant, a molecular weight regulator and a solvent, and sequentially performing a prepolymerization reaction and a final polymerization reaction to obtain a nylon 56 polymer;
[0008] (2) mixing the nylon 56 polymer described in step (1) with a binder and performing melt spinning to obtain a high-strength nylon 56 composite fiber;
[0009] Wherein, the final polymerization reaction in step (1) is carried out under closed conditions;
[0010] The adhesive in step (2) includes one or more of a biological adhesive, a mineral adhesive and a high molecular polymer;
[0011] The mass of the adhesive in step (2) is 1 to 10% of the mass of the nylon 56 polymer.
[0012] Preferably, in the preparation method, the catalyst in step (1) includes one or more of sodium hydroxide, boric acid, toluene diisocyanate, titanium-based catalysts and phosphorus-based catalysts; the titanium-based catalyst includes one or more of titanium dioxide, titanium chloride and titanate; the phosphorus-based catalyst includes one or more of phosphorus-containing inorganic acid catalysts, phosphorus-containing alkane catalysts and phosphorus-containing metal salt catalysts; the phosphorus-containing inorganic acid catalyst includes one or more of phosphoric acid, phosphorous acid and hypophosphorous acid; the phosphorus-containing alkane catalyst includes one or more of alkyl-substituted phosphoric acid, aryl-substituted phosphoric acid and aryl-substituted hypophosphorous acid; the phosphorus-containing metal salt catalyst includes one or more of sodium hypophosphite, sodium metaphosphate and sodium pyrophosphate.
[0013] Preferably, in the preparation method, the antioxidant in step (1) includes one or more of antioxidant 1010, antioxidant DLTDP, antioxidant DSTDP, phenolic antioxidants and amine antioxidants; the phenolic antioxidant is monophenol and / or polyphenol; the amine antioxidant includes one or more of naphthylamine, diphenylamine and p-phenylenediamine.
[0014] Preferably, in the preparation method, the molecular weight regulator in step (1) is phosphorous acid and / or an organic acid; the organic acid is a dibasic acid and / or a monobasic aromatic acid, the dibasic acid includes one or more of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid, dodecanedioic acid and tridecanedioic acid, and the monobasic aromatic acid is benzoic acid and / or phenylacetic acid.
[0015] Preferably, in the preparation method, in step (1), the mass of the nylon 56 salt is 30 to 80% of the sum of the masses of the nylon 56 salt and the solvent; the mass of the catalyst, the antioxidant and the molecular weight regulator are independently 0.01 to 0.5% of the sum of the masses of the nylon 56 salt and the solvent.
[0016] Preferably, in the preparation method, the temperature of the prepolymerization reaction in step (1) is 120 to 200° C., the pressure is 0.5 to 3 MPa, and the time is 0.5 to 8 h.
[0017] Preferably, in the preparation method, in step (1), the temperature of the final polymerization reaction is 220-290° C., and the time is 30-240 min; and vacuuming is further performed after the final polymerization reaction, and the vacuuming time is 10-60 min.
[0018] Preferably, in the preparation method, in step (2), the biological adhesive is animal glue and / or rosin, and the animal glue is shellac and / or hide glue; the mineral adhesive includes one or more of asphalt, ceresin adhesive and sulfur adhesive; the high molecular polymer includes one or more of nylon 510, nylon 512 and nylon 612.
[0019] Preferably, in the preparation method, the temperature of the melt spinning in step (2) is 250 to 290° C., and the drafting ratio is 1.5 to 4 times.
[0020] The invention also provides a high-strength nylon 56 composite fiber prepared by the preparation method.
[0021] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) In the technical scheme of the present invention, the catalyst is conducive to the polymerization reaction, can accelerate the formation of intermolecular hydrogen bonds, and is conducive to the growth of nylon molecular chains; the antioxidant can improve the phenomenon of yellowing of polymers or fibers due to oxidation; the molecular weight regulator can be used as an initiator to initiate the polymerization reaction and control the molecular weight of nylon; the prepolymerization reaction can first cause nylon 56 salt to undergo a dehydration condensation reaction to form a low molecular weight prepolymer, and then discharge water vapor and some by-products out of the kettle; during the final polymerization reaction, nylon 56 salt mainly undergoes a condensation reaction, and by optimizing the final polymerization process conditions (temperature, time), it is conducive to narrowing the molecular weight, increasing the polymer viscosity, and thus increasing the strength and mechanical properties of the nylon 56 composite fiber; the main purpose of adding an adhesive is to add a material with an adhesive effect (such as long-chain nylon, because the long-chain nylon itself has better mechanical properties such as tensile strength and breakage rate than nylon 56), which can reduce the broken fiber rate of nylon 56 polymer during the spinning and stretching process and improve the mechanical properties of the nylon 56 composite fiber. Therefore, the present invention adopts the scheme to co-melt-spin the adhesive and the nylon 56 polymer, and the prepared nylon 56 composite fiber has the advantages of high strength, excellent mechanical properties and low fiber breakage rate.
[0023] (2) The improvement idea of the present invention for nylon 56 salt is not only reflected in the optimization of a single material, but also can be extended to other nylon salts, which has broad expansion potential and application prospects. DETAILED DESCRIPTION
[0024] The present invention provides a method for preparing high-strength nylon 56 composite fiber, comprising the following steps:
[0025] (1) mixing nylon 56 salt, a catalyst, an antioxidant, a molecular weight regulator and a solvent, and sequentially performing a prepolymerization reaction and a final polymerization reaction to obtain a nylon 56 polymer;
[0026] (2) mixing the nylon 56 polymer described in step (1) with a binder and performing melt spinning to obtain a high-strength nylon 56 composite fiber;
[0027] Wherein, the final polymerization reaction in step (1) is carried out under closed conditions;
[0028] The adhesive in step (2) includes one or more of a biological adhesive, a mineral adhesive and a high molecular polymer;
[0029] The mass of the adhesive in step (2) is 1 to 10% of the mass of the nylon 56 polymer.
[0030] In the present invention, the catalyst in step (1) preferably includes one or more of sodium hydroxide, boric acid, toluene diisocyanate, a titanium catalyst and a phosphorus catalyst, and further preferably includes sodium hydroxide, boric acid, toluene diisocyanate, a titanium catalyst or a phosphorus catalyst, and more preferably a phosphorus catalyst.
[0031] In the present invention, the titanium-based catalyst preferably includes one or more of titanium dioxide, titanium chloride, and titanate, more preferably titanium dioxide or titanate, and even more preferably titanium dioxide.
[0032] In the present invention, the phosphorus-based catalyst preferably includes one or more of a phosphorus-containing inorganic acid catalyst, a phosphorus-containing alkane catalyst and a phosphorus-containing metal salt catalyst, more preferably a phosphorus-containing inorganic acid catalyst, a phosphorus-containing alkane catalyst or a phosphorus-containing metal salt catalyst, and more preferably a phosphorus-containing metal salt catalyst.
[0033] In the present invention, the phosphorus-containing inorganic acid catalyst preferably includes one or more of phosphoric acid, phosphorous acid and hypophosphorous acid, more preferably phosphoric acid, phosphorous acid or hypophosphorous acid, and more preferably hypophosphorous acid.
[0034] In the present invention, the phosphorus-containing alkane catalyst preferably includes one or more of alkyl-substituted phosphoric acid, aryl-substituted phosphoric acid and aryl-substituted hypophosphorous acid, more preferably alkyl-substituted phosphoric acid, aryl-substituted phosphoric acid or aryl-substituted hypophosphorous acid, and more preferably aryl-substituted hypophosphorous acid.
[0035] In the present invention, the phosphorus-containing metal salt catalyst preferably includes one or more of sodium hypophosphite, sodium metaphosphate and sodium pyrophosphate, more preferably sodium hypophosphite or sodium metaphosphate, and more preferably sodium hypophosphite.
[0036] In the present invention, the antioxidant in step (1) preferably includes one or more of antioxidant 1010 (tetrakis[3-3',5'-di-tert-butyl-4'-hydroxyphenyl]propionate), antioxidant DLTDP (dilauryl thiodipropionate), antioxidant DSTDP (distearyl thiodipropionate), phenolic antioxidants and amine antioxidants, and further preferably includes one or more of antioxidant 1010, antioxidant DLTDP and antioxidant DSTDP, and more preferably antioxidant 1010.
[0037] In the present invention, the phenolic antioxidant is preferably monophenol and / or polyphenol, more preferably polyphenol; the polyphenol is preferably hydroquinone and / or thiobisphenol, more preferably thiobisphenol.
[0038] In the present invention, the amine antioxidant preferably includes one or more of naphthylamine, diphenylamine and p-phenylenediamine, more preferably naphthylamine, diphenylamine or p-phenylenediamine, and more preferably p-phenylenediamine.
[0039] In the present invention, the molecular weight regulator in step (1) is preferably phosphorous acid and / or an organic acid, more preferably phosphorous acid or an organic acid, and more preferably phosphorous acid.
[0040] In the present invention, the organic acid is preferably a dibasic acid and / or a monobasic aromatic acid, and more preferably a dibasic acid.
[0041] In the present invention, the dibasic acid preferably includes one or more of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid, dodecanedioic acid and tridecanedioic acid, more preferably oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid or benzoic acid, more preferably adipic acid.
[0042] In the present invention, the aromatic acid preferably includes benzoic acid and / or phenylacetic acid, and more preferably is benzoic acid.
[0043] In the present invention, the solvent in step (1) is preferably water.
[0044] In the present invention, the mass of the nylon 56 salt in step (1) is preferably 30-80% of the sum of the mass of the nylon 56 salt and the solvent, more preferably 50-70%, and even more preferably 60%.
[0045] In the present invention, the mass of the catalyst in step (1) is preferably 0.01-0.5% of the sum of the mass of nylon 56 salt and the solvent, more preferably 0.2-0.5%, and even more preferably 0.3%.
[0046] In the present invention, the mass of the antioxidant in step (1) is preferably 0.01-0.5% of the sum of the mass of nylon 56 salt and the solvent, more preferably 0.05-0.2%, and even more preferably 0.1%.
[0047] In the present invention, the mass of the molecular weight regulator in step (1) is preferably 0.01-0.5% of the sum of the mass of nylon 56 salt and the solvent, more preferably 0.1-0.3%, and more preferably 0.15%.
[0048] In the present invention, the temperature of the prepolymerization reaction in step (1) is preferably 120-200°C, more preferably 160-200°C, more preferably 200°C; the pressure is preferably 0.5-3MPa, more preferably 0.5-2MPa, more preferably 0.8-1.5MPa; the time is preferably 0.5-8h, more preferably 1-3h, more preferably 2h.
[0049] In the present invention, after the prepolymerization reaction in step (1), the process preferably further comprises: reducing the pressure to normal pressure. The time for reducing the pressure to normal pressure is preferably 0.1 to 3 hours, more preferably 1 to 2 hours, and more preferably 1.5 hours.
[0050] In the present invention, the temperature of the final polymerization reaction in step (1) is preferably 220-290°C, more preferably 240-280°C, more preferably 260°C; the time is preferably 30-240 min, more preferably 45-90 min, more preferably 60 min; and the pressure is preferably normal pressure.
[0051] In the present invention, the step (1) preferably further comprises vacuuming after the final polymerization reaction. The vacuuming time is preferably 10 to 60 minutes, more preferably 10 to 30 minutes, and more preferably 20 minutes.
[0052] In the present invention, the adhesive in step (2) includes one or more of a biological adhesive, a mineral adhesive and a high molecular polymer, preferably a biological adhesive, a mineral adhesive or a high molecular polymer, and more preferably a high molecular polymer.
[0053] In the present invention, the bioadhesive is preferably animal glue and / or rosin, and more preferably animal glue.
[0054] In the present invention, the animal glue is preferably shellac and / or hide glue, and more preferably shellac.
[0055] In the present invention, the mineral adhesive preferably includes one or more of asphalt, ceresin adhesive and sulfur adhesive, more preferably asphalt or sulfur adhesive, and more preferably asphalt.
[0056] In the present invention, the high molecular polymer preferably includes one or more of nylon 510, nylon 512 and nylon 612, more preferably nylon 510, nylon 512 or nylon 612, and more preferably nylon 510.
[0057] In the present invention, the mass ratio of the adhesive in step (2) is 1 to 10% of the mass of the nylon 56 polymer, preferably 5 to 10%, and more preferably 10%.
[0058] In the present invention, the step (2) of mixing the nylon 56 polymer and the binder preferably includes: crushing the nylon 56 polymer and the binder. The present invention does not limit the size of the crushed particles, and a method known to those skilled in the art can be used.
[0059] In the present invention, the temperature of the melt spinning in step (2) is preferably 250-290°C, more preferably 260-280°C, and more preferably 270°C; the drafting ratio is preferably 1.5-4 times, more preferably 2-3 times, and more preferably 2 times.
[0060] In the present invention, unless otherwise specified, normal pressure refers to one atmosphere.
[0061] The invention also provides a high-strength nylon 56 composite fiber prepared by the preparation method.
[0062] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0063] Example 1
[0064] This embodiment provides a method for preparing a high-strength nylon 56 composite fiber, comprising the following steps:
[0065] (1) 160.18 g of nylon 56 salt, 106.79 g of deionized water, 0.8009 g of sodium hypophosphite, 0.2670 g of antioxidant 1010, and 0.4005 g of phosphorous acid were weighed and added into a reaction kettle, and prepolymerized for 2 h at 200 ° C and 0.8-1.5 MPa; after the prepolymerization was completed, the air release valve was opened and the air was slowly released for 1.5 h to normal pressure, and the temperature was raised to 260 ° C and final polymerization was carried out for 60 min under closed normal pressure conditions; after the final polymerization was completed, vacuum was drawn for 20 min, and the feed valve was opened to pressurize and extrude the material to obtain a nylon 56 polymer, and the molecular weight Mn of the nylon 56 polymer was 25543.
[0066] (2) 50 g of nylon 56 polymer and 0.5 g of long-chain nylon 510 were crushed to 1 mm and mixed, and then put into a melt spinning machine for spinning at a spinning temperature of 270°C and a drafting multiple of 2 times. After winding, high-strength nylon 56 composite fibers were obtained.
[0067] Example 2
[0068] (1) 160.23 g of nylon 56 salt, 106.82 g of deionized water, 0.8012 g of sodium hypophosphite, 0.2671 g of antioxidant 1010, and 0.4005 g of phosphorous acid were weighed and added into a reaction kettle, and prepolymerized for 2 h at 200 ° C and 0.8-1.5 MPa; after the prepolymerization was completed, the air release valve was opened and the air was slowly released for 1.5 h to normal pressure, and the temperature was raised to 260 ° C and final polymerization was carried out for 60 min under closed normal pressure conditions; after the final polymerization was completed, vacuum was drawn for 20 min, and the material was extruded under pressure by opening the feed valve to obtain a nylon 56 polymer, and the molecular weight Mn of the nylon 56 polymer was 26623;
[0069] (2) 50 g of nylon 56 polymer and 2.5 g of long-chain nylon 510 were crushed to 1 mm and mixed, and then put into a melt spinning machine for spinning at a spinning temperature of 270°C and a drafting multiple of 2 times. After winding, high-strength nylon 56 composite fibers were obtained.
[0070] Example 3
[0071] (1) 160.34 g of nylon 56 salt, 106.89 g of deionized water, 0.8017 g of sodium hypophosphite, 0.2673 g of antioxidant 1010, and 0.4008 g of phosphorous acid were weighed and added into a reaction kettle, and prepolymerized for 2 h at 200 ° C and 0.8-1.5 MPa; after the prepolymerization was completed, the air release valve was opened and the air was slowly released for 1.5 h to normal pressure, and the temperature was raised to 260 ° C and final polymerization was carried out for 60 min under closed normal pressure conditions; after the final polymerization was completed, vacuum was drawn for 20 min, and the material was extruded under pressure by opening the feed valve to obtain a nylon 56 polymer, and the molecular weight of the nylon 56 polymer was Mn 26031;
[0072] (2) 50 g of nylon 56 polymer and 5 g of long-chain nylon 510 were crushed to 1 mm and mixed, and then put into a melt spinning machine for spinning at a spinning temperature of 270°C and a drafting multiple of 2 times. After winding, high-strength nylon 56 composite fibers were obtained.
[0073] Example 4
[0074] This embodiment provides a method for preparing a high-strength nylon 56 composite fiber, comprising the following steps:
[0075] (1) 160.94 g of nylon 56 salt, 107.29 g of deionized water, 0.8047 g of sodium hypophosphite, 0.2682 g of antioxidant 1010, and 0.4023 g of phosphorous acid were weighed and added into a reaction kettle, and prepolymerized for 2 h at 200 ° C and 0.8-1.5 MPa; after the prepolymerization was completed, the air release valve was opened and the air was slowly released for 1.5 h to normal pressure, and the temperature was raised to 260 ° C and final polymerization was carried out for 60 min under closed normal pressure conditions; after the final polymerization was completed, vacuum was drawn for 20 min, and the material was extruded under pressure by opening the feed valve to obtain a nylon 56 polymer, and the molecular weight of the nylon 56 polymer was Mn 26410;
[0076] (2) 50 g of nylon 56 polymer and 5 g of long-chain nylon 512 were crushed to 1 mm and mixed, and then put into a melt spinning machine for spinning at a spinning temperature of 270°C and a drafting multiple of 2 times. After winding, high-strength nylon 56 composite fibers were obtained.
[0077] Example 5
[0078] This embodiment provides a method for preparing a high-strength nylon 56 composite fiber, comprising the following steps:
[0079] (1) 160.02 g of nylon 56 salt, 106.68 g of deionized water, 0.8001 g of sodium hypophosphite, 0.2667 g of antioxidant 1010, and 0.4000 g of phosphorous acid were weighed and added into a reaction kettle, and prepolymerized for 2 h at 200° C. and 0.8-1.5 MPa; after the prepolymerization was completed, the air release valve was opened and the air was slowly released for 1.5 h to normal pressure, and the temperature was raised to 260° C. and final polymerization was carried out for 60 min under closed normal pressure conditions; after the final polymerization was completed, vacuum was drawn for 20 min, and the material was extruded under pressure by opening the feed valve to obtain a nylon 56 polymer, and the molecular weight Mn of the nylon 56 polymer was 26848;
[0080] (2) 50 g of nylon 56 polymer and 5 g of long-chain nylon 612 were crushed to 1 mm and mixed, and then put into a melt spinning machine for spinning at a spinning temperature of 270°C and a drafting multiple of 2. After winding, high-strength nylon 56 composite fibers were obtained.
[0081] Comparative Example 1
[0082] This comparative example provides a method for preparing nylon 56 fiber, comprising the following steps:
[0083] (1) 160.10 g of nylon 56 salt, 106.73 g of deionized water, 0.8005 g of sodium hypophosphite, 0.2668 g of antioxidant 1010, and 0.4002 g of phosphorous acid were weighed and added into a reaction kettle, and prepolymerized for 2 h at 200 ° C and 0.8-1.5 MPa; after the prepolymerization was completed, the air release valve was opened and the air was slowly released for 1.5 h to normal pressure, and the temperature was raised to 260 ° C and final polymerization was carried out for 60 min under closed normal pressure conditions; after the final polymerization was completed, vacuum was drawn for 20 min, and the material was extruded under pressure by opening the feed valve to obtain a nylon 56 polymer, and the molecular weight Mn of the nylon 56 polymer was 25436;
[0084] (2) The nylon 56 polymer was crushed into 1 mm and then put into a melt spinning machine for spinning at a spinning temperature of 270°C and a drafting multiple of 2. After winding, nylon 56 fibers were obtained.
[0085] Comparative Example 2
[0086] This comparative example provides a method for preparing nylon 56 fiber, comprising the following steps:
[0087] (1) 160.26 g of nylon 56 salt, 106.84 g of deionized water, 0.8013 g of sodium hypophosphite, 0.2671 g of antioxidant 1010, and 0.4007 g of phosphorous acid were weighed and added into a reaction kettle, and prepolymerized for 2 h at 200 ° C and 0.8-1.5 MPa; after the prepolymerization was completed, the air release valve was opened and the air was slowly released for 1.5 h to normal pressure, and the temperature was raised to 260 ° C and final polymerization was carried out for 60 min under closed normal pressure conditions; after the final polymerization was completed, vacuum was drawn for 20 min, and the material was extruded under pressure by opening the feed valve to obtain a nylon 56 polymer, and the molecular weight Mn of the nylon 56 polymer was 26475;
[0088] (2) The nylon 56 polymer was crushed into 1 mm and then put into a melt spinning machine for spinning at a spinning temperature of 290°C and a drafting multiple of 2. After winding, nylon 56 fibers were obtained.
[0089] Comparative Example 3
[0090] This comparative example provides a method for preparing nylon 56 fiber, comprising the following steps:
[0091] (1) 160.14 g of nylon 56 salt, 106.76 g of deionized water, 0.8007 g of sodium hypophosphite, 0.2669 g of antioxidant 1010, and 0.4004 g of phosphorous acid were weighed and added into a reaction kettle, and prepolymerized for 2 h at 200 ° C and 0.8-1.5 MPa; after the prepolymerization was completed, the air release valve was opened and the air was slowly released for 1.5 h to normal pressure, and the temperature was raised to 260 ° C and final polymerization was carried out for 60 min under closed normal pressure conditions; after the final polymerization was completed, vacuum was drawn for 20 min, and the material was extruded under pressure by opening the feed valve to obtain a nylon 56 polymer, and the molecular weight Mn of the nylon 56 polymer was 25272;
[0092] (2) The nylon 56 polymer was crushed into 1 mm and then put into a melt spinning machine for spinning at a spinning temperature of 260°C and a drafting multiple of 2. After winding, nylon 56 fibers were obtained.
[0093] Comparative Example 4
[0094] This comparative example provides a method for preparing nylon 56 composite fiber, comprising the following steps:
[0095] (1) 160.05 g of nylon 56 salt, 106.70 g of deionized water, 0.8003 g of sodium hypophosphite, 0.2668 g of antioxidant 1010, and 0.4001 g of phosphorous acid were weighed and added into a reaction kettle, and prepolymerized for 2 h at 200 ° C and 0.8-1.5 MPa; after the prepolymerization was completed, the air release valve was opened and the air was slowly released for 1.5 h to normal pressure, and the temperature was raised to 260 ° C and final polymerization was carried out for 60 min under closed normal pressure conditions; after the final polymerization was completed, vacuum was drawn for 20 min, and the material was extruded under pressure by opening the feed valve to obtain a nylon 56 polymer, and the molecular weight Mn of the nylon 56 polymer was 25304;
[0096] (2) 50 g of nylon 56 polymer and 10 g of long-chain nylon 510 were crushed to 1 mm and mixed, and then put into a melt spinning machine for spinning at a spinning temperature of 270°C and a drafting multiple of 2 times. After winding, high-strength nylon 56 composite fibers were obtained.
[0097] Test Example 1
[0098] (1) Using an Ubbelohde viscometer at 25±0.01° C., the relative viscosities of the fiber products obtained in Examples 1 to 5 and Comparative Examples 1 to 4 were measured in a 96% concentrated sulfuric acid solution with a concentration of 0.01 g / mL;
[0099] (2) The fineness of the fibers obtained in Examples 1 to 5 and Comparative Examples 1 to 4 was measured according to the method of GB / T 14343-2003;
[0100] (3) The breaking strength and breaking elongation of the fibers obtained in Examples 1 to 5 and Comparative Examples 1 to 4 were measured according to the method of GB / T 14344-2008.
[0101] The results of Test Example 1 are shown in Table 1.
[0102] Table 1. Results of Test Example 1
[0103]
[0104] As shown in Table 1, after adding long-chain high molecular weight nylon polymer, the breaking strength and breaking elongation of nylon 56 fiber will increase, and its mechanical properties are better than pure nylon 56 fiber without adding long-chain nylon, and the nylon 56 composite fiber obtained by adding long-chain high molecular weight nylon polymer PA510 has higher strength and is more suitable for PA56 spinning. However, when the addition amount of long-chain high molecular weight nylon polymer is higher than 10wt% of nylon 56 polymer, the mechanical properties such as strength and breaking elongation of nylon 56 composite fiber are not as good as when the addition amount is 1-10%. This is because the addition amount of long-chain high molecular weight nylon polymer is too much, and the two cannot be well fused together after melting, resulting in stratification, resulting in poor mechanical properties.
[0105] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing high-strength nylon 56 composite fiber, characterized in that: The following steps are involved: (1) mixing nylon 56 salt, a catalyst, an antioxidant, a molecular weight regulator and a solvent, and sequentially performing a prepolymerization reaction and a final polymerization reaction to obtain a nylon 56 polymer; (2) mixing the nylon 56 polymer described in step (1) with a binder and performing melt spinning to obtain a high-strength nylon 56 composite fiber; Wherein, the final polymerization reaction in step (1) is carried out under closed conditions; The adhesive in step (2) includes one or more of a biological adhesive, a mineral adhesive and a high molecular polymer; The mass of the adhesive in step (2) is 1 to 10% of the mass of the nylon 56 polymer.
2. The preparation method according to claim 1, characterized in that: The catalyst in step (1) includes one or more of sodium hydroxide, boric acid, toluene diisocyanate, titanium catalyst and phosphorus catalyst; the titanium catalyst includes one or more of titanium dioxide, titanium chloride and titanate; the phosphorus catalyst includes one or more of phosphorus-containing inorganic acid catalysts, phosphorus-containing alkane catalysts and phosphorus-containing metal salt catalysts; the phosphorus-containing inorganic acid catalyst includes one or more of phosphoric acid, phosphorous acid and hypophosphorous acid; the phosphorus-containing alkane catalyst includes one or more of alkyl-substituted phosphoric acid, aryl-substituted phosphoric acid and aryl-substituted hypophosphorous acid; the phosphorus-containing metal salt catalyst includes one or more of sodium hypophosphite, sodium metaphosphate and sodium pyrophosphate.
3. The preparation method according to claim 1 or 2, characterized in that: The antioxidant in step (1) includes one or more of antioxidant 1010, antioxidant DLTDP, antioxidant DSTDP, phenolic antioxidants and amine antioxidants; the phenolic antioxidant is monophenol and / or polyphenol; the amine antioxidant includes one or more of naphthylamine, diphenylamine and p-phenylenediamine.
4. The preparation method according to claim 3, characterized in that: The molecular weight regulator in step (1) is phosphorous acid and / or an organic acid; the organic acid is a dibasic acid and / or a monobasic aromatic acid, the dibasic acid includes one or more of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid, dodecanedioic acid and tridecanedioic acid, and the monobasic aromatic acid is benzoic acid and / or phenylacetic acid.
5. The preparation method according to claim 1 or 4, characterized in that: In step (1), the mass of the nylon 56 salt is 30-80% of the sum of the mass of the nylon 56 salt and the solvent; the mass of the catalyst, the antioxidant and the molecular weight regulator are independently 0.01-0.5% of the sum of the mass of the nylon 56 salt and the solvent.
6. The preparation method according to claim 5, characterized in that: The temperature of the prepolymerization reaction in step (1) is 120-200° C., the pressure is 0.5-3 MPa, and the time is 0.5-8 h.
7. The preparation method according to claim 1 or 6, characterized in that: In step (1), the temperature of the final polymerization reaction is 220-290° C., and the time is 30-240 min. After the final polymerization reaction, vacuuming is also performed, and the time of vacuuming is 10-60 min.
8. The preparation method according to claim 1, characterized in that: In step (2), the biological adhesive is animal glue and / or rosin, and the animal glue is shellac and / or hide glue; the mineral adhesive includes one or more of asphalt, ceresin adhesive and sulfur adhesive; the high molecular polymer includes one or more of nylon 510, nylon 512 and nylon 612.
9. The preparation method according to claim 1 or 8, characterized in that: The temperature of the melt spinning in step (2) is 250-290° C., and the drafting ratio is 1.5-4 times.
10. The high-strength nylon 56 composite fiber obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Composite modified chinlon preparation method and application
CN108677268A
Novel chinlon material preparation technology capable of achieving bending by adopting bio-based chinlon 56 as body
CN111748869A
Preparation method of high-fluidity polyamide 56 fiber
CN111876840A
Preparation method and application of low-rheology low-yellowing nylon
CN118325072A
Optically anisotropic spinning solution comprising a mixture of p-aramid and aliphatic polyamide, and fibres to be made therefrom
WO1997033022A1